2020
DOI: 10.3390/ijms21207585
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Regulatory Module Reveals Associations of Microgravity with Dysfunctions of Multi-body Systems and Tumorigenesis

Abstract: Previous studies have demonstrated that microgravity could lead to health risks. The investigation of the molecular mechanisms from the aspect of systems biology has not been performed yet. Here, we integratively analyzed transcriptional and post-transcriptional regulations based on gene and miRNA expression profiles in human peripheral blood lymphocytes cultured in modeled microgravity. Two hundred and thirty dysregulated TF-miRNA (transcription factor and microRNA) feed-forward loops (FFLs) were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…RWV exposure of PBMC results in a multi-cellular immunosuppressive response that may contribute to the impairment of the immune system and the defense against pathogens [ 144 ]. A further study investigated transcriptional and post-transcriptional regulations based on gene and miRNA expression profiles in human peripheral blood lymphocytes exposed to the RWV [ 145 ]. Two hundred and thirty dysregulated TF-miRNA (transcription factor and microRNA) feed-forward loops (FFLs) were identified in s-µ g .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RWV exposure of PBMC results in a multi-cellular immunosuppressive response that may contribute to the impairment of the immune system and the defense against pathogens [ 144 ]. A further study investigated transcriptional and post-transcriptional regulations based on gene and miRNA expression profiles in human peripheral blood lymphocytes exposed to the RWV [ 145 ]. Two hundred and thirty dysregulated TF-miRNA (transcription factor and microRNA) feed-forward loops (FFLs) were identified in s-µ g .…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred and thirty dysregulated TF-miRNA (transcription factor and microRNA) feed-forward loops (FFLs) were identified in s-µ g . Associations of RWV exposure with dysfunctions of multi-body systems and tumorigenesis were reported [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
“…Combining these novel technologies with microgravity platforms could be used to uncover immunotherapy drug targets and provide further insight into disease specific immune responses. Research has shown that microgravity has a positive impact on combating diseases such as cancer by regulating cancer cell proliferating and survival [142][143][144]. The mechanisms found can be used to benefit cancer treatment on Earth.…”
Section: Technological Advances For Future Microgravity Researchmentioning
confidence: 99%
“…Another study used systems biological methods and performed an integrative analysis of regulatory module and found associations of µg with dysfunctions of various systems and tumorigenesis [19]. Analysis of the skeletal system revealed that most of the genes and miRNAs in the subnetwork were involved in bone loss.…”
Section: Breast Cancer Cells In Microgravity: New Aspects For Cancer Researchmentioning
confidence: 99%
“…Analysis of the skeletal system revealed that most of the genes and miRNAs in the subnetwork were involved in bone loss. The analysis of the relationship between µg (RWV) and 20 cancer types showed that most cancers might be promoted by µg [19].…”
Section: Breast Cancer Cells In Microgravity: New Aspects For Cancer Researchmentioning
confidence: 99%